PERANCANGAN DESIGN UI/UX PADA WEBSITE TOKO MISTER SHOP ID MENGGUNAKAN METODE DESIGN THINKING - Rani Puspita; Rina Astriani (Asosiasi Dosen Muda Indonesia, 2023)
This research aims to help people find the items they need more easily and to make the purchasing process smoother. To create this website, the author will use a program called Figma. Design thinking is the approach that will be used to design this website. This approach focuses on finding solutions based on what customers need. This website will hopefully provide better options for customers who wish to purchase additional parts for Vespa motorbikes. By using design thinking, this design will understand what customers need, will create a website appearance that is easy to understand, and will add features that make the purchasing process simpler.Keywords: New Media, Social Media, Instagram, Media Exposure, Followers Satisfaction, Automotive.